Isolated Central Nervous System Involvement after Brentuximab Vedotin Treatment for HIV-Positive ALK-Negative Anaplastic Large Cell Lymphoma - Takuya Suyama; Kumiko Matsui; Kosuke Makihara; Masatoshi Tsuru (Case Reports in Hematology)
Human immunodeficiency virus (HIV)-associated lymphoma poses a high mortality risk despite antiretroviral therapy (ART). Although intermediate- or high-grade B-cell lymphomas are common, anaplastic large-cell lymphomas (ALCLs) are rare and seldom affect the central nervous system (CNS). Herein, we present a case of HIV-associated ALCL with isolated CNS involvement that occurred following the discontinuation of ART that was administered after treatment with brentuximab vedotin (BV)—which does not cross the blood-brain barrier. At the time of CNS recurrence, the patient’s CD4 count was 9 cells/mm3. This is the first report of CNS recurrence in HIV-associated ALCL. Considering the high risk of CNS relapse, we suggest initiating CNS prophylaxis in cases of HIV-associated ALCL, particularly in patients receiving CNS-impermeable agents such as BV.